Comparative Pathomorphological Characteristics of Placental Vessels from Pregnancies with High and Low Risk of Preeclampsia - Kamilya Makhambetova; Yevgeniy Kamyshanskiy; Olga Ponamareva; Zhanna Amirbekova; Nazerke Oshakhtiyeva (Ķazaķstannyṇ Klinikalyķ Medicinasy)
Relevance: Preeclampsia is a common multisystem specific pregnancy disorder accompanied by remodeling of placental vessels. Vascular structural changes are influenced by both systemic factors and local anomalies, such as umbilical cord pathology. The large variability and inconsistency of histomorphometric changes in placental vessels as markers of placental dysfunction emphasize the need for their further research using standardized methods of morphometric analysis.